PERANCANGAN DAN EVALUASI USER INTERFACE WEBSITE PEMESANAN DAN RESERVASI CAFE KAHURIPAN DENGAN DESIGN THINKING - Ismi Aziz, Ahun; Prasetyo, Novian Adi; Sidiq, Muhammad Fajar (Universitas Islam Balitar, 2023)
Cafe Kahuripan is a business engaged in the culinary field where customers can order menus and rent a place. Currently, the process of ordering menus and renting a place is done manually with customers coming directly to the place or contacting the admin via WhatsApp listed on Facebook. However, there is a decrease in subscribers from 2021 to 2022 due to a lack of marketing which is only limited to Facebook and Whatsapp. To overcome these problems, it is necessary to design a website as a solution to make it easier for customers to order menus and rent places online. In this design, it is necessary to pay attention to a good User Interface (UI) in order to increase the level of user trust and satisfaction. The website must also have easy access that can be done anywhere. Cafe Kahuripan website user interface design uses the design thinking method. The design of the user section, there are several pages such as home, about us, menu, reservation, contact us, order status and reservation status. The design of the admin section, there is an admin dashboard, customer data, menus, orders and reviews. The result of this study is the design of the user interface for the Cafe Kahuripan website from the user side (front-end), which allows users to order menus and rent places online. The results of the usability testing which obtained an average score of 79 is a good achievement and indicates that the UI design that has been carried out has succeeded in meeting user needs. Hypothesis analysis shows that the hypothesis H0 is rejected and H1 is accepted, this is in accordance with the average score of the System Usability Scale (SUS). Respondents' feedback was analyzed and improved according to the suggestions given based on the priority level to produce a better website for users.